Transformación del método cartesiano en las ediciones de la geometría de Bernard Lamy - Bello-Chavez, Jhon (Revista Científica, 2020)
This article presents a contribution to the history of the teaching of algebra, the study of the Cartesian method of solving geometric problems in the different editions of the book Les Élémens de Géométrie (Lamy, 1685). This textbook circulated in France for almost a century, was used in colleges of the congregation of the Oratorians and established a teaching model of geometry that developed the analysis proposed in the Géométrie (Descartes, 1637). When analyzing the section on the method in the editions of the book from 1685 to 1756 it was evident that the teaching focused on developing a technique by means of rules to use the analysis. In each edition the importance of the diagrams in the application of the method was decreasing and the construction of the solution of equations of first and second degree was losing importance. As a Cartesian, Lamy resorted to the simplicity principle of this philosophy and method, therefore, he used relationships between lines described by means of proportionality and the similarity of triangles as a means to organize their justifications.